(3JYdjbGJ GdcjajIs - (3GdbGSe Hf CMeO Hf MejO Hf CMeO GdeMdj GdUfYGfj GdQUGUs ((3UdGM Hf Ydi Hf eMeO Hf CHj GdbGSe Hf eMeO Hf LYaQ Hf GdMSjf GdgGOhi s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe CMeO GdQUGU aUd ai cjajGJ KHhJ GdUaGJ hGdCMLGe heG jJUd HPdc (B: (3EYde Cf GdUaGJ hGdCMcGe s
(3BNQgG (B:s
(3aCeG EPG LYd GdaUd GdKGdK hgh GdcdGe ai cTagG Yf ebJVGgG aebJVGgG gh Mce eG ENJU HgG ef ZjQ RjGOI JeJ JYdjbI GdcjajI HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG HYV GdJUMjMGJs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda SfI (B857s
Keywords: (3GdeYGQa GdYGeIs